From pathogenesis to current treatment of the cutaneous psoriasis - a literature review - Jakubowska, Wiktoria; Pisera, Piotr; Kiełkowicz, Aleksandra; Pactwa, Filip; Popińska, Zuzanna; Ślusarczyk, Daniel; Żmuda, Bartłomiej; Żuberek, Michał (Journal of Education, Health and Sport, 2023)
Introduction: Psoriasis is a chronic inflammatory autoimmune disease that can be divided into several subtypes based on the areas of the body occupied by the lesions and the severity of the disease. The overall prevalence of psoriasis ranges from 0 to 11,8%. The disease occurs with equal frequency in both sexes. PsO cannot be completely cured, so many patients experience stigma and have diminished self-esteem due to the characteristic appearance of the lesions. Aim of the study: The purpose of the study is to summarize the available knowledge about classification and options for psoriasis treatment. The options in diagnosis and treatment, including the latest methods, were described and summarized. Materials and methods: Literature available in the PubMed database was reviewed using the following keywords: “Psoriasis”, “Nail Psoriasis”, “Psoriasis Vulgaris”, “Psoriasis Treatment”, “New Psoriasis Treatment”, “Psoriasis Classification”, “Biologic Therapy for Psoriasis”, “Systemic Therapy for psoriasis”. Conclusions: Psoriasis is a genetic skin condition mediated by the immune system. The underlying mechanisms entail intricate interactions between the innate and adaptive immune system. There are various indices for assessing the severity of psoriasis, the most commonly used of which is PASI(Psoriasis Area and Severity Index). Retinoids, cyclosporine and methotrexate are the non-biologic therapies most frequently employed for moderate to severe psoriasis treatment, while topical therapy, which includes mainly corticosteroids and vitamin D analogues, is a successful approach for effectively managing mild psoriasis.